Computer forensics with FTK : enhance your computer forensics knowledge through illustrations, tips, tricks, and practical real-world scenarios /: enhance your computer forensics knowledge through illustrations, tips, tricks, and practical real-world scenarios. (2014) - Unknown
No abstract available